From Chrysalis to Winged Dreams (2011)
This text gives voice to Juliana Villada, mentor in Expeditions to knowledge: "Thanks to the environmental education program Love for Nature, of the Solidarity Support Foundation of the Municipality of El Retiro, FASOR, my colleagues and I, advised by Professor Nora Londoño, created the research hotbed Winged Dreams. With the support of the project Ondas of Colciencias, we started a research project about butterflies"